Estimation of mercury background values in sediment and biota of the Bijagós archipelago, Guinea-Bissau. Issue 1 (15th October 2016) - Coelho, J.P.; Monteiro, R.J.R.; Catry, T.; Lourenço, P.M.; Catry, P.; Regalla, A.; Catry, I.; Figueira, P.; Pereira, E.; Vale, C.; P.Granadeiro, José
Abstract: This work evaluates the mercury (Hg) contamination status (sediments and biota) of the Bijagós archipelago, off the coast of Guinea-Bissau. Sediments exhibited very low concentrations (< 1–12 ng g −1 ), pointing to negligible sources of anthropogenic Hg in the region. Nevertheless, Hg is well correlated to the fine fraction, aluminium, and loss on ignition, indicating the effect of grain size and organic matter content on the presence of Hg in sediments. Mercury in the bivalves Tagelus adansoni and Senilia senilis did not vary considerably among sites, ranging within narrow intervals (0.09–0.12 and 0.12–0.14 μg g −1 (dry weight), respectively). Divergent substrate preferences/feeding tactics may justify slight differences between species. The value 11 ng g −1 is proposed as the sediment background concentration for this West-African coastal region, and concentrations within the interval 8–10 ng g −1 (wet weight) may be considered as reference range for S. senilis and T. adansoni in future monitoring studies. Highlights: Low Hg content in sediments and biota of the Bijagós archipelago, Guinea-Bissau. Species specific traits may justify differences between bivalves. The sediment background concentration of 11 ng g − 1 is proposed for this region. The interval 8–10 ng g − 1 is suggested as reference range for the studied biota.